(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Prisoners, despite being incarcerated, retain their basic human rights, including the right to dignified living conditions, adequate food, and proper nutrition. The living conditions in prison significantly impact their physical and mental well-being, affecting their chances of rehabilitation and reintegration into society. Many prisons in India and worldwide face overcrowding, poor sanitation, inadequate healthcare, and insufficient food supply, leading to severe health issues among inmates. The United Nations Standard Minimum Rules for the Treatment of Prisoners (Nelson Mandela Rules) and Indian legal frameworks, including Article 21 (Right to Life) and Article 47 (State’s Duty to Improve Nutrition & Public Health) of the Indian Constitution, emphasize that prisoners must receive adequate nutrition and humane living conditions.